التعايش بين نباتات الفصيلة القرنية والبكتيريا المثبتة للأزوت الهوائي دراسة حالة نبات الفول دراسة مقارنة ومراجعة - عبسي, سعيدة; مدلل, إبتسام; سعودي, لينة; مليك, كريمة (جامعة الوادي - university of eloued, 2022)
This work aims to study the symbiotic relationship between nitrogen-fixing bacteri and Bean (Viciafaba L.). After research, investigation and investigation, studies reported that co-inoculation of bacterial strains significantly improves nitrogen uptake and reduces by 50% treatment with chemical fertilizers while maintaining bean productivity at high levels. The bacterial strains also proved effective in fixing nitrogen in saline soils, and boron and zinc they play an important role in many physiological functions during the symbiotic relationship, where boron helps in the process of cross-pollination with rhizobia and increase the yield of the plant, and zinc also promotes the formation and development of nitrogen-fixing nodes .
التنوع الحيوي وفيزيولوجيا النبات
Keywords: الفول; Bean (Vicia faba L.); Symbiotic relationship; Nitrogen-fixing Bacteria; Rhizobia; Nitrogen.